Transmission of musical knowledge and history of European culture in the early decades of the 15th century - Nanni, Matteo (Musica Docta, 2014)
The evolution of music history in the first half of the 14th century is characterized by an internationalization of European musical culture, as a continuation of the cultural process of early Humanism. The category of ‘evolution’, and the very idea of ‘rebirth’, or the “legend of progress” (Martin Le Franc, Johannes Tinctoris) as discussed by Reinhard Strohm, must be read today not only in terms of stylistic standardization, but also as one of the hallmarks of a search for cultural identity. Even from a historical-musical point of view, what we see is the building of a new European taste from the combination of local styles and practices, thanks to the spread of handwritten collections all over the continent. Even composers from more distant regions embraced the new style, although less regularly. The Council of Basel was not only a historical event confined to the years during which the synod took place, just as it cannot be regarded as a mere empirical fact that only affected one city in northern Switzerland. It should rather be taken as a paradigmatic event in the cultural history of the 14th century. The encounters between intellectuals and artists, the interaction between musicians from different European regions, who met thanks to the frequent travels of the courts and chapels, turned the Council into a virtual platform for both the search for a new cultural identity, and the birth of new musical repertories and practices. The Council therefore transcends the material boundaries of the city of Basel, turning into a true ‘cultural generator’, where each individual contributed to the constant transmission and fusion of musical experiences, which became vectors for a new musical vision that reached to even the farthest corners of Europe.